PENATAAN HALAMAN RUMAH PADA LAHAN TERBATAS DI ERA HUNIAN MINIMALIS - Andin rusyana; Ghaniyya Putri Salsabila; Haura Adzkia Yumna; Kania Anggita Putri; Yani Achdiani; Gina Indah Permata Nastia (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2026)
ABSTRACT Rapid urban development has increased the demand for residential land, resulting in a reduction of green open spaces, including home yards. The growing density of buildings and land conversion in urban areas have further limited the availability of green spaces within residential environments. This condition is exacerbated by the trend of minimalist housing on limited land, causing home yards to be underutilized. This study aims to analyze the utilization of home yards in limited-land housing, identify challenges in their arrangement, and formulate functional, aesthetic, and environmentally friendly landscaping strategies. The study employed a qualitative method with a literature review approach. Data were obtained from 25 scientific publications published between 2020 and 2025 related to household green space management and minimalist housing, and were analyzed descriptively through data reduction, categorization, thematic interpretation, and conclusion drawing. The findings indicate that the low level of home yard optimization is influenced by limited land availability, inadequate public literacy regarding small-space design, and low awareness of the importance of household-scale green spaces. Applicable strategies include vertical gardens, the use of pots and tiered plant racks, the selection of adaptive ornamental plants, and the development of medicinal plant gardens. The novelty of this study lies in the integration of aesthetic, productive, and ecological functions into a conceptual model for home yard arrangement on limited land. In conclusion, optimizing home yards not only enhances residential aesthetics but also contributes to improved air quality, reduced stormwater runoff, and greater microclimatic comfort. ABSTRAK Perkembangan wilayah perkotaan yang pesat meningkatkan kebutuhan lahan permukiman dan menyebabkan berkurangnya ruang terbuka hijau, termasuk halaman rumah. Kepadatan bangunan dan alih fungsi lahan di kawasan perkotaan semakin membatasi keberadaan ruang hijau pada lingkungan hunian. Kondisi ini diperparah oleh tren hunian minimalis berlahan sempit sehingga halaman rumah sering tidak dimanfaatkan secara optimal. Penelitian ini bertujuan menganalisis pemanfaatan halaman rumah pada hunian berlahan terbatas, mengidentifikasi permasalahan penataannya, serta merumuskan strategi penataan yang fungsional, estetis, dan ramah lingkungan. Penelitian menggunakan metode kualitatif dengan pendekatan studi pustaka. Data diperoleh dari 30 literatur ilmiah terbitan 2020–2025 yang relevan dengan penataan ruang hijau rumah tangga dan hunian minimalis, kemudian dianalisis secara deskriptif melalui reduksi data, kategorisasi, interpretasi tematik, dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa rendahnya optimalisasi halaman rumah dipengaruhi oleh keterbatasan lahan, minimnya literasi desain ruang sempit, dan rendahnya kesadaran terhadap pentingnya ruang hijau rumah tangga. Strategi yang dapat diterapkan meliputi taman vertikal, penggunaan pot dan rak tanaman bertingkat, pemilihan tanaman adaptif, serta pengembangan apotek hidup. Kebaruan penelitian terletak pada integrasi fungsi estetika, produktif, dan ekologis dalam model penataan halaman rumah berlahan terbatas. Kesimpulannya, optimalisasi halaman rumah tidak hanya meningkatkan estetika hunian, tetapi juga mendukung kualitas udara, mengurangi limpasan air hujan, dan meningkatkan kenyamanan mikroklimat.